2022
DOI: 10.1002/pro.4483
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of insertions and extensions in the functional evolution of the ribonucleotide reductase family

Abstract: Ribonucleotide reductases (RNRs) are used by all free‐living organisms and many viruses to catalyze an essential step in the de novo biosynthesis of DNA precursors. RNRs are remarkably diverse by primary sequence and cofactor requirement, while sharing a conserved fold and radical‐based mechanism for nucleotide reduction. In this work, we expand on our recent phylogenetic inference of the entire RNR family and describe the evolutionarily relatedness of insertions and extensions around the structurally homologo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…The amino acid sequence of PcNrdD suggests that it belongs to the formate-requiring class III RNRs (Burnim et al , 2022b; Wei et al ., 2014), and initial optimization of the assay composition showed that this was the case (Figure 1 - figure supplement 1). ATP-cone mediated activation of PcNrdD enzyme activity by ATP or inhibition by dATP was tested with two different substrates.…”
Section: Resultsmentioning
confidence: 99%
“…The amino acid sequence of PcNrdD suggests that it belongs to the formate-requiring class III RNRs (Burnim et al , 2022b; Wei et al ., 2014), and initial optimization of the assay composition showed that this was the case (Figure 1 - figure supplement 1). ATP-cone mediated activation of PcNrdD enzyme activity by ATP or inhibition by dATP was tested with two different substrates.…”
Section: Resultsmentioning
confidence: 99%
“…Ribonucleotide reductases (RNRs) are essential enzymes in all free-living organisms, as they enable the only de novo synthesis pathway of 2′-deoxyribonucleotides, the building blocks for DNA ( 1 ). Despite wide evolutionary diversity ( 2 , 3 ), all RNRs share a common catalytic mechanism initiated by the formation of a thiyl radical on a conserved active-site cysteine ( 4 ). The oxygen-dependent class I RNRs ( 5 , 6 ) are used by aerobic life, including most eukaryotes, many prokaryotes, and associated viruses ( 2 , 3 ).…”
Section: Main Textmentioning
confidence: 99%
“…Despite wide evolutionary diversity ( 2 , 3 ), all RNRs share a common catalytic mechanism initiated by the formation of a thiyl radical on a conserved active-site cysteine ( 4 ). The oxygen-dependent class I RNRs ( 5 , 6 ) are used by aerobic life, including most eukaryotes, many prokaryotes, and associated viruses ( 2 , 3 ). These RNRs have long fascinated researchers for their relevance as drug targets and for their dynamic quaternary structure involving two subunits (Figure 1A): 1) a small ferritin-like subunit (β) that houses a stable radical cofactor, and 2) a large catalytic subunit (ɑ) that contains the nucleotide-binding sites, including the active site, an allosteric site that controls substrate specificity, and additional allosteric sites involved in regulating overall enzyme activity.…”
Section: Main Textmentioning
confidence: 99%
“…Another limitation of traditional ASR methods for generating functional sequences is that insertions and deletions (indels) and mishandled or ignored by maximum likelihood sequence evolution models. As indel events are often responsible for driving functional diversification [46][47][48][49] , we also developed an automated pipeline for the maximum likelihood reconstruction of insertions/deletions (indels) in large ancestral sequence databases produced with mASR (SI Fig 1) . For site n, all tips are assigned a binary label (0 for no indel, 1 for indel), depending on whether a gap character is observed.…”
Section: Multiplexed Ancestral Sequence Reconstruction For Protein Re...mentioning
confidence: 99%